Restorative Justice as a Mechanism for Resolving Intra-Family Theft Offenses: A Legal Analysis of Reconciliation-Based Criminal Settlement in Indonesia - Awanda Handani; Dadan Taufik Fathurohman (PT. Caesarindo Triloka Persada, 2026)
Intra-family theft offenses present a distinct challenge in criminal law because the consequences of such offenses extend beyond material losses and affect trust, emotional relationships, and family stability. Unlike ordinary theft cases, offenses committed within family relationships require a careful balance between enforcing criminal responsibility and preserving social bonds. Although restorative justice has been increasingly recognized within the Indonesian criminal justice system, its application in intra-family theft cases remains insufficiently examined, particularly regarding its legal framework, implementation mechanism, and contribution to reconciliation. This study examines the role of restorative justice in resolving intra-family theft offenses through a reconciliation-based criminal settlement approach under Indonesian criminal law. This research employs normative juridical analysis using statutory, conceptual, and case approaches by examining relevant legal provisions, restorative justice regulations, and legal practices. The findings indicate that restorative justice provides an alternative settlement mechanism through voluntary mediation, offender accountability, restitution, and reconciliation between victims and offenders. The effectiveness of this approach is influenced by the willingness of offenders to acknowledge responsibility, the voluntary participation of victims, the restoration of losses, and the ability of mediators to facilitate balanced agreements. Restorative justice offers a more appropriate approach for intra-family theft offenses by integrating criminal accountability with social restoration, reducing unnecessary criminalization, and maintaining family relationships.